Teaching English to Young Learners: Supporting the Case for the Bilingual Native English Speaker Teacher. Issue 3 (1st September 2016) - Copland, Fiona; Yonetsugi, Eli
Abstract: The growing number of young children around the world learning English has resulted in an increase in research in the field. Many of the studies have investigated approaches to learning and teaching, with a particular emphasis on effective pedagogies (e.g. Harley 1998; Shak and Gardner 2008). Other studies have focused on the linguistic gains of children (e.g. Smojver 2015) and on the complexities researching children entails (see Pinter 2011 for an excellent overview). However, despite calls in the literature, few studies have examined in detail the effects on young children (ages 5–10 years) of the teacher using different languages in the classroom, that is, L1 and L2. The study reported here addresses this issue. Drawing on interactional data from two NEST (native English speaker teacher) classrooms, interviews with NESTs and homeroom teachers, and from the NESTs' diaries, it examines the effects of languages used by two NESTs on young children's learning. One NEST understands and can use the children's L1; the other only understands and uses L2. We will show that in the context of the young learner classroom, teachers who know the children's L1 have a greater repertoire of teaching skills and so can provide more language learning opportunities for language learning. This reality, we believe, supports the case for employing bilingual teachers wherever possible for the young learner classroom.